2017
DOI: 10.1152/ajpendo.00098.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac overexpression of perilipin 2 induces dynamic steatosis: prevention by hormone-sensitive lipase

Abstract: Cardiac intracellular lipid accumulation (steatosis) is a pathophysiological phenomenon observed in starvation and diabetes mellitus. Perilipin 2 (PLIN2) is a lipid droplet (LD)-associated protein expressed in nonadipose tissues, including the heart. To explore the pathophysiological function of myocardial PLIN2, we generated transgenic (Tg) mice by cardiac-specific overexpression of PLIN2. Tg hearts showed accumulation of numerous small LDs associated with mitochondrial chains and high cardiac triacylglycerol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 54 publications
5
36
0
Order By: Relevance
“…It may be that the energetic needs of an E4 astrocyte in the absence of robust glucose metabolism overpower the inhibitory effect of PLIN2 on LD lipolysis. The overexpression of PLIN2 has also been shown to increase LD formation in various cell types [46,47,48]. This is congruent with our findings in regards to E4 astrocytes, where an increase in LD number paralleled with increased PLIN2 expression.…”
Section: Discussionsupporting
confidence: 92%
“…It may be that the energetic needs of an E4 astrocyte in the absence of robust glucose metabolism overpower the inhibitory effect of PLIN2 on LD lipolysis. The overexpression of PLIN2 has also been shown to increase LD formation in various cell types [46,47,48]. This is congruent with our findings in regards to E4 astrocytes, where an increase in LD number paralleled with increased PLIN2 expression.…”
Section: Discussionsupporting
confidence: 92%
“…123 It has reportedly been demonstrated that overexpression of PLIN2 is sufficient to increase lipid droplet formation, while the downregulation of PLIN2 reduces lipid droplet formation in a wide range of cells, indicating that PLIN2 can actively determine lipid droplet pool size. 123,135,136 PLIN2 protein levels closely correlate with cellular triglyceride contents in beta cells as well. 123,135,136 PLIN2 protein levels closely correlate with cellular triglyceride contents in beta cells as well.…”
Section: Plin2 the Most Abundant Plin In Beta Cellsmentioning
confidence: 93%
“…123 In nonbeta cells, the modulation of PLIN2 expression is reported to affect multiple aspects of cellular lipid handling, including FA uptake, beta-oxidation, and activation of nuclear receptors in the liver, heart, macrophages, and white adipocytes. 123,135,136 PLIN2 protein levels closely correlate with cellular triglyceride contents in beta cells as well. PLIN2 protein is increased in beta cell lines, mouse islets, and human islets after fatty acid loading in vitro and in islets from obese mice (high-fat diet, ob/ob mice) and fasted mice.…”
Section: Plin2 the Most Abundant Plin In Beta Cellsmentioning
confidence: 93%
“…The expression levels of three proteins involved in the transport of long chain fatty acids are altered, too, including glutamic-oxaloacetic transaminase 2 (Got2), perilipin 2 (Plin2), and solute carrier family 27 (Table 4). Got2 and Plin2 upregulation in the heart has been shown to lead to accumulation of lipid droplets (Holloway et al, 2011;Ueno et al, 2017). Interestingly, the expression levels of solute carrier family 27 have been suggested to positively correlate with fatty acid uptake (Milger et al, 2006), but also lipid oxidation (Jeppesen et al, 2012).…”
Section: Molecular Transportmentioning
confidence: 99%